2022
DOI: 10.1007/s10517-022-05424-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hypervirulent K. pneumoniae and Problems of Health-Care Associated Infections

Abstract: The review describes virulence factors of hypervirulent K. pneumoniae (hvKp) including genes determining its virulence and discusses their role in the development of health-care associated infections. The contribution of individual virulence factors and their combination to the development of the hypervirulence and the prospects of using these factors as biomarkers and therapeutic targets are described. Virulence factors of hvKp and “classical” K. pneumoniae strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 166 publications
1
1
0
Order By: Relevance
“…Additionally, Nirwati et al (2019) reported that 85.63% of Kp isolates were biofilm producers, and 64.7% of these isolates were strong biofilm producers, according to a related study by Hassan et al (2011) [ 73 , 74 ]. Our data also showed no differences in the biofilm formation of hmvKp and non-hmvKp phenotypes among each strong, moderate, and weak biofilm-forming isolates; these results were consistent with clinical isolates investigated in Soto et al’s study [ 75 , 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, Nirwati et al (2019) reported that 85.63% of Kp isolates were biofilm producers, and 64.7% of these isolates were strong biofilm producers, according to a related study by Hassan et al (2011) [ 73 , 74 ]. Our data also showed no differences in the biofilm formation of hmvKp and non-hmvKp phenotypes among each strong, moderate, and weak biofilm-forming isolates; these results were consistent with clinical isolates investigated in Soto et al’s study [ 75 , 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, most of the clinically isolated hvKPs were sensitive to commonly used clinical antibiotics, and the resistance rates were significantly lower than cKP, which was consistent with the previous studies ( 5 , 37 ). But in the past years, hvKP has become a clinical challenge in China ( 4 , 30 ), because the proportion of hvKP isolates increased from 25.5% to 54.5% within 2 years, and it resisted all testing resistant, except carbapenems and amikacin ( 32 ). Zhang et al ( 38 ) first reported the detection of carbapenem-resistant hypervirulent KP (CR-hvKP).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria have been a major cause of death among enteric bacteria with drug-resistant cases. The biofilm forming ability allows it to colonize the host tissues and medical devices, survive in hostile environments, and resist antibiotics and host immune response (Tutelyan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%